2021
DOI: 10.1007/s10570-021-04096-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the whiteness index of cotton fabric with a least squares model

Abstract: The textile bleaching process that involves hot hydrogen peroxide (H 2 O 2 ) solution is commonly practised in cotton fabric manufacture. The purpose of the bleaching process is to remove color from the cotton, achieving a permanent white before proceeding to dyeing or shape matching. Normally, the visual ratings of whiteness on the cotton are measured based on whiteness index (WI). However, it is found that there is little research on chemical predictive modelling of the cotton fabric's WI compared to experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…According to Satrio et al 47 , negative R 2 values indicate a large gap between the observed and predicted values; in this case, the fuzzy technique in this investigation yielded extremely dissimilar results. This is because the training data creates rules and criteria that form the basis of the fuzzy method's membership function, fuzzy logic operators, and if–then statements 19 . An assortment of fuzzy rules, a database detailing the membership functions used by the fuzzy rules, and a reasoning mechanism outlining the inference path upon the rules to adopt projected data are the three parts of this framework 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Satrio et al 47 , negative R 2 values indicate a large gap between the observed and predicted values; in this case, the fuzzy technique in this investigation yielded extremely dissimilar results. This is because the training data creates rules and criteria that form the basis of the fuzzy method's membership function, fuzzy logic operators, and if–then statements 19 . An assortment of fuzzy rules, a database detailing the membership functions used by the fuzzy rules, and a reasoning mechanism outlining the inference path upon the rules to adopt projected data are the three parts of this framework 48 .…”
Section: Resultsmentioning
confidence: 99%
“…The LSSVR model is a nonlinear prediction method based on support vector machine theory (SVM). When it comes to decreasing the computational burden associated with reducing the number of viable classes, LSSVR delivers a more efficient response than the SVM by applying a separate set of linear equations in dual space 19 , 20 . In recent years, academics from a broad range of disciplines have devoted increasing amounts of attention and interest throughout the course of many years.…”
Section: Introductionmentioning
confidence: 99%
“…The above WI CIE index is limited to the value 40 < WI CIE < 5Y − 280. The investigations on the predictive modelling of the cotton fabric’s whiteness index, in COT-NaOH-H 2 O 2(as) for various reagent concentrations and bleaching conditions, were carried out recently [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, to validate the optimization, experimental runs were performed at suggested optimum conditions. The actual values of responses were compared against predicted responses by a method prescribed by Yeo and Lau (2021) with little modification (Equation (7)): %prediction error=()actual valuegoodbreak−predicted value2actual value×100 …”
Section: Methodsmentioning
confidence: 99%